2018
DOI: 10.6001/fil-soc.v29i1.3630
|View full text |Cite
|
Sign up to set email alerts
|

The Utilitarian Aspect of the Philosophy of Ecology: The Case of Corporate Social Responsibility

Abstract: This study aims to combine the philosophical perspective and the practical ethics of ecology in the everyday with a more pragmatic concept of corporate social responsibility. The importance of the latter is shown to be based in the abandonment of the distinction of subject and object and the development of personal as well as cultural ecological consciousness embedded in the notion of unity between man and nature. This philosophical shift in the consciousness is also reflected in terms of utility. Hence, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The benefits of environmental projects have been noted by many researchers (Drejeris & Ozeliene, 2019). A number of scientific works prove the correlation between the implementation of corporate social responsibility policies and sales growth (Saeidi et al, 2018). Implementation of corporate social responsibility of manufacturers and importers in the field of ecology is more profitable than paying an environmental fee.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of environmental projects have been noted by many researchers (Drejeris & Ozeliene, 2019). A number of scientific works prove the correlation between the implementation of corporate social responsibility policies and sales growth (Saeidi et al, 2018). Implementation of corporate social responsibility of manufacturers and importers in the field of ecology is more profitable than paying an environmental fee.…”
Section: Resultsmentioning
confidence: 99%
“…e emphasis on the virtues of Confucianism that human should respect for nature has a positive influence on ecological education [22]. Studies have found that ecological awareness affects people's sense of social responsibility, which in turn affects people's behaviour and practices [23]. And, corporate social responsibility induces firms to create value for the environment and society and reduce the occurrence of environmental problems [24].…”
Section: China Joint Presidential Statement On Climate Change On 25mentioning
confidence: 99%
“…According to S.P. Saeidi and et al (2018) developing CSR projects helps an organization build a better reputation amongst internal and external stakeholders, and through attracting talent, motivating, recruiting and retaining employees, also CSR can help satisfy a variety of organizational members' psychological or developmental needs (Gond, 2017). Gond et al argued that CSR can be directed towards employees as well as prospective employees and can be an appropriate tool for enhancing corporate image and reputation (Verčič, Corric 2018).…”
Section: Corporate Social Responsibility and Its Links To Organizational Culturementioning
confidence: 99%